The Effect Of Cervical Cancer Education Videos And Iva Examinations On The Knowledge And Attitudes Women Of Reproductive Age - Ridhotul Janah; Dyah Retnoningrum; Marleni (Journal of Innovative and Creativity, 2025)
Cervical cancer is the second leading cause of death in women globally, with high incidence and mortality rates in developing countries, including Indonesia. Low coverage of early detection, often below five percent, causes many cases to be diagnosed at an advanced stage. The main problem identified is the lack of knowledge and positive attitudes of Women of Childbearing Age (WUS) towards early detection of cervical cancer through Visual Inspection with Acetic Acid (IVA) examination. This study aims to determine the effect of cervical cancer educational videos and VIA examinations on improving the knowledge and attitudes of women of childbearing age in the Gerunggang Community Health Center working area in 2025. The research method used is quantitative with a quasi-experimental design of one-group pretest-posttest. The study population was 205 women of childbearing age, with a sample of 32 women of childbearing age selected using a purposive sampling technique. Data were collected through questionnaires before and after the educational video was given. Data analysis used a paired sample t-test. The results showed a significant increase in women of childbearing age knowledge scores, from an average of 90.09 to 90.72 (p = 0.000). Similarly, the attitude score of women of childbearing age increased from an average of 76.12 to 89.88 (p = 0.000). The conclusion of this study is that the educational video significantly influenced the increase in knowledge and the formation of positive attitudes among women of childbearing age towards IVA screening. Therefore, the Gerunggang Community Health Center is recommended to routinely use this audiovisual media in its cervical cancer early detection education program.